Insights Into the Links Between Proteostasis and Aging From C. elegans - Zhang, William Hongyu; Koyuncu, Seda; Vilchez, David (Frontiers in Aging, 2022)
Protein homeostasis (proteostasis) is maintained by a tightly regulated and interconnected network of biological pathways, preventing the accumulation and aggregation of damaged or misfolded proteins. Thus, the proteostasis network is essential to ensure organism longevity and health, while proteostasis failure contributes to the development of aging and age-related diseases that involve protein aggregation. The model organism Caenorhabditis elegans has proved invaluable for the study of proteostasis in the context of aging, longevity and disease, with a number of pivotal discoveries attributable to the use of this organism. In this review, we discuss prominent findings from C. elegans across the many key aspects of the proteostasis network, within the context of aging and disease. These studies collectively highlight numerous promising therapeutic targets, of which may one day facilitate the development of interventions to delay aging and prevent age-associated diseases.